LEVEL OF COMPETENCY AND EXTENT OF TRAINING NEEDS ON TECHNOLOGY LITERACY AMONG THE STAFF OF GOVERNMENT OFFICES IN CATANDUNAES - Tapado, Belen Molin (Journal of Technology Management and Business, 2016)
Â The study assessed the level of competency and the extent of training needs for technology literacy among the staff of the government offices in Catanduanes, Philippines. Along the areas of Computer Operation, WordProcessing, Spreadsheet, Database Management Systems, Internet Services, Computer Programming, Management Information Systems, Systems Analysis and Design (SAD) and Network Design and Management or Administration.Â  This study made use of a descriptive-survey method wherein a questionnaire was used to determine the level of competencies of the staff on computer literacy and the extent of their training needs on the specified technology literacy areas.Â Â  Level of Competency and Extent of Training Needs were measured using a 5-point Likert Scale. Result of the study showed that the staff of the government offices in Catanduanes evaluated themselves as â€œslightly competentâ€ on the first four technology literacy skills that include: (a) computer operation skills, (b) word processing, (c) spreadsheet, (d) database management and â€œnot competentâ€ on the next five technology literacy skills that were: (a) using the Internet Services, (b) computer programming, (c) SAD/Software Engineering,Â  (d) MIS and (e) network design & management which means that the staff on the average, have a little knowledge and skills along technology Â literacy needed by an office worker hence these staff felt they needed much training for technology literacy. The development and improvement of the knowledge and skills of the government staff in their literacy on the specified technology areas should be the done by the management of the government offices since office transactions nowadays are automated and dependent on information system applications and use of computing resources. Likewise, productivity is enhanced in employing technologies as tools in doing office transactions. Improvement of government staffâ€™s performance would mean satisfied clientele and achievement of the mission, vision, goals and objectives of the organization